2023
DOI: 10.2147/idr.s421299
|View full text |Cite
|
Sign up to set email alerts
|

Refractory Palmoplantar Pustulosis Successfully Treated with JAK Inhibitor Tofacitinib: A Case Series

Abstract: Background: Palmoplantar pustulosis (PPP) is a common chronic and recurrent skin disease of the palms and soles with significant pain, mental distress, and functional disability. PPP is challenging to treat and usually requires prolonged management. Therapy resistance and frequent relapse discourages patients from follow-up. No unified standard and no published therapeutic guidelines have yet been defined on PPP treatment. In general, all therapeutic options known for autoimmune diseases, psoriasis in particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Furthermore, tofacitinib, a JAK inhibitor, has been shown in multiple studies to alleviate refractory PPP. This treatment rapidly reduces the severity of skin lesions, such as erythema, aseptic pustules, and desquamation (85,86). The findings of this research strongly endorse the future target of JAK/STAT3 signaling in PPP and offer genetic evidence for the use of tofacitinib in the treatment of refractory PPP.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, tofacitinib, a JAK inhibitor, has been shown in multiple studies to alleviate refractory PPP. This treatment rapidly reduces the severity of skin lesions, such as erythema, aseptic pustules, and desquamation (85,86). The findings of this research strongly endorse the future target of JAK/STAT3 signaling in PPP and offer genetic evidence for the use of tofacitinib in the treatment of refractory PPP.…”
Section: Discussionmentioning
confidence: 99%
“…A 45-year-old woman with plaque psoriasis and painful pustules on her palms and soles showed significant improvement in joint symptoms and lesion clearance after three months of tofacitinib ( 15 ). Another study involving six patients aged 42–58 with PPP demonstrated substantial improvement with tofacitinib, with all patients achieving at least a 50% reduction in palmoplantar pustular psoriasis area and severity index (PPPASI) after four weeks, and half experiencing more than an 80% reduction ( 16 ).…”
Section: Discussionmentioning
confidence: 99%